Use of mercury isotopes to quantify sources of human inorganic mercury exposure and metabolic processes in the human body - Buyun Du; Runsheng Yin; Xuewu Fu; Ping Li; Xinbin Feng; Laurence Maurice (Environment International, 2021)
The pathways of human mercury (Hg) exposure are complex and accurate understanding of relative contributions from different pathways are crucial for risk assessment and risk control. In this study, we determined total Hg concentration and Hg isotopic composition of human urine, dietary components, and inhaled air in the Wanshan Hg mining area (MA), Guiyang urban area (UA), and Changshun background area (BA) to understand Hg exposure sources and metabolic processes in human body. At the three studied sites, total gaseous mercury (TGM) showed negative δ202Hg (−3.11‰ to + 1.12‰) and near-zero Δ199Hg (−0.16‰ to + 0.13‰), which were isotopically distinguishable from Hg isotope values of urine (δ202Hg: −4.02‰ to − 0.84‰; Δ199Hg: −0.14‰ to 0.64‰). We observed an offset of −1.01‰ to −1.6‰ in δ202Hg between TGM and urine samples, and an offset of −1.01‰ to 0.80‰ in δ202Hg between rice and urine samples, suggesting that lighter isotopes are more easily accumulated in the kidneys and excreted by urine. We proposed that the high positive Δ199Hg in urine samples of UA was derived from fish consumption. The results of a binary mixing model based on Δ199Hg were compared with those from a classic dietary model. The results from the MIF binary model showed that fish consumption accounted for 22% of urine Hg in the families at UA, whereas fish consumption contributed limited Hg to MA and BA. This study highlighted that Hg isotopes can be a useful tracer in understanding the sources and fates of Hg in human bodies.